2019
DOI: 10.1111/andr.12664
|View full text |Cite
|
Sign up to set email alerts
|

Expression of miRNA‐371a‐3p in seminal plasma and ejaculate is associated with sperm concentration

Abstract: Background: The microRNAs of the miR-371-3 cluster are novel serum markers for testicular germ cell tumors. Sporadic reports suggested the expression of this miRNA in semen. Objectives: To verify the expression of miR-371a-3p in seminal plasma and unprocessed ejaculate; to compare seminal plasma miRNA levels in germ cell tumors patients with those of controls; to look for an association of miRNA levels with semen quality. Materials and methods: The miR-371a-3p expression was analyzed with qPCR. The study popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 39 publications
(45 reference statements)
2
21
0
Order By: Relevance
“…Assessment of miR-371a-3p in the same azoospermic seminal plasma cohort in which we assessed CRIPTO concentration similarly revealed higher basal levels than in blood sera (as had been reported previously [20,33]) and levels not significantly differing from normospermic males (Table 4, Figure 5B). We did detect miR-371a-3p in the obstructive azoospermia and non-obstructive azoospermia cohorts, as well as the TGCT cohort and single GCNIS-only sample, which is similar to a previous report [20]. In the non-obstructive azoospermia samples, we also found the highest average miR-371a-3p reading in the group with the lower Johnsen's score; we hypothesize this may be due to a cell-type dilution effect as we described above for CRIPTO.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Assessment of miR-371a-3p in the same azoospermic seminal plasma cohort in which we assessed CRIPTO concentration similarly revealed higher basal levels than in blood sera (as had been reported previously [20,33]) and levels not significantly differing from normospermic males (Table 4, Figure 5B). We did detect miR-371a-3p in the obstructive azoospermia and non-obstructive azoospermia cohorts, as well as the TGCT cohort and single GCNIS-only sample, which is similar to a previous report [20]. In the non-obstructive azoospermia samples, we also found the highest average miR-371a-3p reading in the group with the lower Johnsen's score; we hypothesize this may be due to a cell-type dilution effect as we described above for CRIPTO.…”
Section: Discussionsupporting
confidence: 79%
“…Relative levels of miR-371a-3p have been shown to be positively correlated with sperm concentration [19,20], so it was suggested that this microRNA could function as a surrogate of germ cell composition/niche in males. In this work, as for CRIPTO, we found a positive correlation between miR-371a-3p and the VCM index (although not statically significant; Figure 6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This assumption is supported by the findings of Boellaard et al who recently documented the presence of miR-371a-3p in normal testicular tissue and its absence in other parts of the urogenital tract [27]. As miR-371 has been shown to be specifically associated with human stem cells [28][29][30] and as it is found in seminal plasma, too [31,32], it is rational to assume that this miR is specifically generated by normal testicular germ cells and most probably even more by the cells of GCT. In serum, patients with nonseminomas showed significantly higher miR-371a-3p expression, and CS2/3 patients had higher levels than those with CS1 [5].…”
Section: Mir-371a-3p Levels In the Tissues Of Tumor And Contralateralmentioning
confidence: 58%
“…One study examined systematically all elements of the male urogenital tract that can contribute microRNA to ejaculate and demonstrated that miR‐371a‐3p in healthy men is solely derived from germ cells, with levels correlating to some extent with sperm concentration (Boellaard et al , ). The other study also detected miR‐371a‐3p in seminal fluid of men without TGCT and found positive correlation with sperm concentration and total sperm count (Radtke et al , ). Although it remains to be sorted out which types of germ cells secrete the miR‐371a‐3p and in which maturation stage the levels are highest, the findings of the two studies open a possibility of using the miR‐371a‐3p as a novel biomarker for stages of spermatogenesis in patients with infertility.…”
mentioning
confidence: 84%